A novel approach to laboratory assessment and reporting of platelet von Willebrand factor. (17th February 2022) - Kragh, Thorsten; Pekrul, Isabell; Ott, Helmut W.; Spannagl, Michael; Möhnle, Patrick
Abstract: The interaction of platelets with von Willebrand factor is essential for primary hemostasis. Concentration and activity of plasma von Willebrand factor are routine parameters in the assessment of hemostasis disorders. In addition to plasma von Willebrand factor, platelet von Willebrand factor, synthesized in megakaryocytes and stored in α-granules of circulating platelets, is known to contribute to primary hemostasis and the microenvironment of thrombus formation. The laboratory assessment of platelet von Willebrand factor however is cumbersome and not widely established as a routine parameter. We here propose a method for laboratory assessment and reporting of platelet von Willebrand factor potentially useful for laboratory routines in specialized laboratories. Our model allows to describe platelet von Willebrand factor as 1. the concentration of platelet von Willebrand factor in whole blood, 2. the amount of platelet von Willebrand factor in a sample with a defined concentration of 1000 platelets/nl, and 3. the concentration of platelet von Willebrand factor in one platelet. According to our results in healthy individuals, the proportion of platelet von Willebrand factor activity is estimated to be about 10% of total von Willebrand factor in human plasma under physiological circumstances. The concentration of platelet von Willebrand factor is estimated to be 0.4 IU/ml in a sample with a defined concentration of 1000 platelets/nl and to be about 42 IU/ml in one platelet (both expressed as VWF:Ag).